If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -11 = -3x + 7 Reorder the terms: -11 + -6x = -3x + 7 Reorder the terms: -11 + -6x = 7 + -3x Solving -11 + -6x = 7 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -11 + -6x + 3x = 7 + -3x + 3x Combine like terms: -6x + 3x = -3x -11 + -3x = 7 + -3x + 3x Combine like terms: -3x + 3x = 0 -11 + -3x = 7 + 0 -11 + -3x = 7 Add '11' to each side of the equation. -11 + 11 + -3x = 7 + 11 Combine like terms: -11 + 11 = 0 0 + -3x = 7 + 11 -3x = 7 + 11 Combine like terms: 7 + 11 = 18 -3x = 18 Divide each side by '-3'. x = -6 Simplifying x = -6
| ((S+1)(4-s^2))=0 | | 72=18e | | 0.05(7t-4)=0.35(t-3)+0.85 | | 33n+60= | | -9y-6x=0 | | x+x+3x-10=180 | | 33n+6= | | 24r+48= | | m^2-3=29 | | 28u+14= | | 19d=57 | | 10/x=65/40 | | 13x+4y=20000 | | 81z+45= | | 90+2x-6+x=180 | | 32=2(w)+2(4+3w) | | 14*e=2*7 | | m+6+(4m+2)= | | 25a=35 | | 4=y+20 | | 110x+10= | | 42t+7= | | 7/x=2/1.8 | | 2(4v-9)-3(v-11)=-52 | | 2x+6+(6x-1)= | | 2x-y+3z= | | 1-2x=5-6 | | 5/-12 | | -7y=-x+12 | | 1-((x-2)/3) | | 3x+-12=3x+-12 | | .333(3.14)r^2(8.5)=142 |